2014
DOI: 10.1177/0020764014543711
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and correlates of severe social withdrawal (hikikomori) in Hong Kong: A cross-sectional telephone-based survey study

Abstract: The study finds that the prevalence of severe social withdrawal in Hong Kong is comparable to that in Japan. Both groups with withdrawal behaviors for more or less than 6 months share similar characteristics and are related to other contemporary youth issues, for example, compensated dating and self-injury behavior. The self-perceived non-problematic group appears to be a distinct group and the withdrawal behaviors of its members may be discretionary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
143
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(163 citation statements)
references
References 22 publications
18
143
2
Order By: Relevance
“…Having said that, these youths may still need to be engaged very proactively with persistency because they might not have the confidence or interpersonal skills to socialize with strangers, including both laymen and professionals, initially. It is noteworthy that based on the previous findings on the possible change of social withdrawal levels (Wong et al, 2014), when this type of socially withdrawn youth withdraw for a lengthy period of time, some may have more severe social withdrawal condition similar to the overdependent youths. But the underlying process remains the same.…”
Section: The Second Type Of Social Withdrawal Processmentioning
confidence: 88%
See 2 more Smart Citations
“…Having said that, these youths may still need to be engaged very proactively with persistency because they might not have the confidence or interpersonal skills to socialize with strangers, including both laymen and professionals, initially. It is noteworthy that based on the previous findings on the possible change of social withdrawal levels (Wong et al, 2014), when this type of socially withdrawn youth withdraw for a lengthy period of time, some may have more severe social withdrawal condition similar to the overdependent youths. But the underlying process remains the same.…”
Section: The Second Type Of Social Withdrawal Processmentioning
confidence: 88%
“…3 months) as problematic. Wong et al (2014) compared the number of negative life events and the poor mental health status of youths who have been socially withdrawn for more than 6 months and less than 6 months and found that they are very similar. In other words, it seems that there is not much difference between youths who have been withdrawn for 3 months and those who have been withdrawn for 6 months or more.…”
Section: Duration Of Withdrawalmentioning
confidence: 99%
See 1 more Smart Citation
“…In Hong Kong, a telephone-based epidemiological survey has revealed that hikikomori sufferers (duration 6 months and over) account for 1.9% of the population. 45 Just recently, we conducted an epidemiological survey focusing on young people in urban areas of mainland China -Beijing, Shanghai, and Shenzhenthrough socialnetworking services and revealed the existence of hikikomori in mainland China. 46,47 34 ).…”
Section: Multidimensional Understandings Of Hikikomorimentioning
confidence: 99%
“…One form of social withdrawal that has been most commonly described in Japan is hikikomori. It is characterized by persistently reclusive behavior and has a lifetime prevalence of 1-2% in East Asian countries (Koyama et al, 2010;Teo and Gaw, 2010;Wong et al, 2014). Substantial debate exists over whether hikikomori is a unique psychiatric condition or a cultural concept of distress that reflects other underlying psychopathology.…”
Section: To the Editorsmentioning
confidence: 99%